Cyber Security through Password Management Strategies - Varshney, Monika; Shrivastava, Azad Kumar; Aggarwal, Alok; Kumar, Adarsh (International Journal of Computer Sciences and Engineering, 2018)
Out of various cyber security measures password is one the most crucial measure especially due to exponential growth of Internet and multi-media users after the advent of these services over mobile gadget. This work focusses on password management strategies in context of cyber safety. Different password cracking techniques have been used by hackers in past which had been varying with the changing paradigms related to population growth and its literacy level. Recent password cracking techniques used in 2017 are analyzed. Permutation and combinations used for password strength are discussed with a mathematical model which gives how long will it take to crack a password over different machines. Two case studies for password operations have been discussed by taking Windows and Unix operating systems. For making a password a strong unbreakable password hashing & salting techniques are analyzed.